Implementation of the Ternakloka Application membership method in increasing livestock sales in Kota Pari Village - Wahyuni, Sri; Sari, Dini Julia; Hernawaty, Hernawaty; Afifah, Nur (International Conference on Sciences Development and Technology, 2022)
Livestock has an important role in improving the economy of rural communities. However, there are still obstacles faced by breeders in Kota Pari Village. The main problems are the sale of livestock, difficulties in promoting livestock or bringing livestock to traditional markets and the involvement of middlemen in the process of buying and selling livestock. Overcoming these problems, the researchers implemented the website-based Ternakloka membership application membership method. The membership method which is based on fuzzy set theory allows for more flexible classification of data into categories. This study tested the Ternakloka application using the membership method in Kota Pari Village. The results of this implementation indicate a significant increase in the availability of livestock information to potential buyers. The evaluation results show that the Ternakloka application with the membership method has succeeded in increasing efficiency and transparency in selling livestock in Kota Pari Village. With better information accessibility and implementation of a more effective marketing strategy, livestock sales have increased which has a positive impact on the economy of the farming community. This research provides evidence that the use of livestock application technology using the membership method can be an innovative solution and has the potential to improve the welfare of farmers and encourage the growth of the livestock industry in rural areas.